Frekuensi Genotip dan Alel Gena Sulfonylurea Receptor-1 (sur1) pada Subjek Diabetes Melitus Tipe 2 Suku Jawa - YUNITA LINAWATI (Fakultas Farmasi Universitas Pancasila, 2011)
Type 2 diabetes is a metabolic disorder that results from insulin secretion disorder, insulin action or both. SUR1 gene is part of KATP channel in the pancreatic β-cell that plays an essential role related with cell membrane depolarization and glucose-induced insulin secretion. The polymorphism p.R1273R of SUR1 gene, causes KATP channel failed to give feedback to metabolic activation, failed of closing KATP channel, reduces insulin secretion, impaired glucose tolerance, and causes type 2 diabetes. This is case-control study using 80 subjects consist of 40 subjects with type 2 diabetes as case and 40 subjects of non diabetes as control. The SUR1 gene p.R1273R polymorphism genotyping were detected by PCRRFLP. Data were statistically analyzed by t-test, Chi-Square. The genotype frequency distribution of p.R1273R SUR1 gene in type 2 diabetes subjects were 90% of GG genotype and 10% of AG genotype. In non diabetes subjects, GG genotype was 87,5% and AG genotype was 12.5%. In type 2 diabetes and non diabetes subjects the AA genotype was not observed. The allele frequency distribution in type 2 diabetes subjects G allele was 95% and A allele was 5%, in non diabetes subjects G allele was 93.75% and A allele was 6.25%. All the genotype and allele frequency distributions in type 2 diabetes and non diabetes subjects were not statistically significant (p = .723 genotype frequency; p = 0.732 allel frequency).